Vegetative Propagation of Medicinal Plant on Sambiloto (Andrographis paniculata (Burm.f.) Wall. ex Nees) - Solikin (Research Perspective on Biological Science Vol. 1, 2025)
Aims: To determine the effect of node stem cuttings position on the growth and yield of sambiloto (Andrographis paniculata (Burm. f.) Wall. ex Nees. It belongs to the family Acanthaceae, which has been cultivated and grows widely in Indonesia. Methodology: The experiment was conducted in Purwodadi Botanic Garden in February-May 2017 at an altitude of 300 m above sea level. An experimental study design was followed for the study. The study used a randomized block design with the treatment of node position of stem cuttings, i.e. top, middle, and basal parts. Each treatment was replicated three times. Results: The top stem cutting produced the highest cutting life, leaf area, leaf dry weight, root, and generative organs dry weight. In contrast, the basal stem cutting produced the lowest live cutting and plant growth. Conclusion: The top stem cutting propagation of sambiloto produced the highest plant survival and growth with cutting life, leaf area, leaf dry weight and total dry weight of 100%, 162.40 cm2 per plant, 0.49 g per plant, 1.03 g per plant, respectively.